2014
DOI: 10.3133/ofr20141225
|View full text |Cite
|
Sign up to set email alerts
|

Ecological implications of Laurel Wilt infestation on Everglades Tree Islands, southern Florida

Abstract: For more information on the USGS-the Federal source for science about the Earth, its natural and living resources, natural hazards, and the environment-visit http://www.usgs.gov or call 1-888-ASK-USGS (1-888-275-8747)For an overview of USGS information products, including maps, imagery, and publications, visit http://www.usgs.gov/pubprodTo order this and other USGS information products, visit

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
1
6
0
1
Order By: Relevance
“…Impact of laurel wilt disease, especially on mature trees, has been extensive resulting in tree populations that are highly biased towards the smallest trunk diameters. These results are consistent with other studies [1,14] that also reported populations of redbay are highly biased toward the smallest trunk diameters. Apparently, these small saplings (or possibly underground suckers attached to the roots of nearby mature trees) are too small for effective colonization of X. glabratus and, hence, spread of the fungus to these diminutive individuals.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Impact of laurel wilt disease, especially on mature trees, has been extensive resulting in tree populations that are highly biased towards the smallest trunk diameters. These results are consistent with other studies [1,14] that also reported populations of redbay are highly biased toward the smallest trunk diameters. Apparently, these small saplings (or possibly underground suckers attached to the roots of nearby mature trees) are too small for effective colonization of X. glabratus and, hence, spread of the fungus to these diminutive individuals.…”
Section: Discussionsupporting
confidence: 93%
“…Although laurel wilt disease was only introduced to U.S. in the last 15-20 years, it has rapidly spread throughout the southeastern states including Georgia and Florida; besides redbay and swampbay, laurel wilt has spread to other native members of the Lauraceae including silkbay (P. humilis), sassafras (Sassafras albidium), and pondspice [1,13,16]. Results from the current study are consistent with other reports documenting the disease as it infests and moves through an area or ecosystem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the fungi turned out to be pathogenic and have killed millions of naive host trees. In the 10 years since the invasion into the southeastern United States of the Asian beetle Xyleborus glabratus and its previously unknown mycobiont Raffaelea lauricola, over 500 million trees in the family Lauraceae have been killed (94). Avocado production in Florida and elsewhere is also at risk (94).…”
Section: Introductionmentioning
confidence: 99%
“…In the 10 years since the invasion into the southeastern United States of the Asian beetle Xyleborus glabratus and its previously unknown mycobiont Raffaelea lauricola, over 500 million trees in the family Lauraceae have been killed (94). Avocado production in Florida and elsewhere is also at risk (94). This was impossible to predict because there was no information about these species before they became invasive.…”
Section: Introductionmentioning
confidence: 99%